Assessing the Appropriateness of Three-Dimensional Conformal Radiotherapy Technique Planning Treatment for Rectal Versus Cervical Cancer: A Comparative Study - Ruaa Emad Al-Khalidi; Nashwan Karkhi Abdulkareem; Arthur Saniotis; Rojgar Najat Yousif (Diyala Journal of Medicine, 2025)
Background: Radiotherapy is an important part of the treatment paradigm for many patients with rectal and cervical malignancies. With the development of more powerful 3D conformal treatment planning tools, the clinical application of three-dimensional conformal radiation therapy (3D-CRT) has gained recognition for its potential to enhance treatment results for these patients. Objective: To assess which cancer type benefits more from the (3D-CRT) technique by comparing its effectiveness for rectal and cervical cancer, with a focus on dosimetric outcomes. Patients and Methods: A retrospective analysis conducted from August 2023 to January 2024 assessed ten cases of rectal cancer and ten cases of cervical cancer, who treated with 3D-CRT technique at Awat Radiation Oncology Center (AROC), Erbil. Many dosimetric parameters, including mean dose (Dmean), minimum dose (Dmin), maximum dose (Dmax), target volume coverage (D95%), homogeneity index HI, conformity index CI, and the dose that is received by the organ at risk, have been evaluated in order to determine the efficacy of 3D-CRT technique for both cancers. Results: Rectal cancer showed higher conformity and homogeneity index in the PTV int_sum phase (0.87 ± 0.05), (0.16 ± 0.02) compared to cervical cancer (0.66 ± 0.21), (0.19 ± 0.01), indicating better alignment of prescribed dose with target volume and more consistent dose distribution within the target volume. For organs small bowel (V45 < 195cc) and bladder (V45 < 50%), rectal cancer exhibits very high significantly superior sparing in comparison to cervical cancer, displaying lower average volumes and percentages of these organs receiving 45 Gy (p <0.001 for both). Conclusion: The investigation demonstrated that 3D-CRT offered better target coverage, dose homogeneity, and conformity for rectal cancer. Plans for rectal cancer also showed improved bladder and rectum sparing. Keywords: Rectal cancer, Cervix cancer, Homogeneity index (HI), Conformity index (CI).